Facile Synthesis of Fluorescent Carbon Quantum Dots with High Product Yield Using a Solid-Phase Strategy - Ren, Haitao; Qi, Fan; Feng, Xiangbo; Liu, Jiaxiang; Zhao, Yuzhen (Molecules (Basel, Switzerland), 2024)
The liquid-phase method is the most commonly utilized strategy for synthesizing fluorescent carbon quantum dots (CQDs). However, the liquid-phase synthesis of CQDs faces challenges such as low yield, complex purification, and the use of toxic solvents, which limit large-scale production and practical applications. In this study, fluorescent CQDs with a high product yield of 78% were synthesized using glucose as a carbon source through a green and facile one-step solid-phase approach, without solvents or post-treatment. A systematic study of the structure and fluorescence properties of the synthesized CQDs was conducted using various characterization techniques. The results indicated that the mean size of obtained CQDs was 4.1 nm, and that their surface had abundant oxygen-containing functional groups, resulting in favorable water solubility. The synthesized CQDs exhibited excitation-dependent fluorescence, with optimal excitation and emission wavelengths at 358 and 455 nm, respectively. Additionally, the CQDs solution showed bright blue fluorescence under 365 nm UV light, with a quantum yield of 6.21% and a fluorescence lifetime of 3.02 ns. This study offers valuable insights into the green and efficient synthesis of fluorescent CQDs powder.